2021
DOI: 10.4103/ijo.ijo_2390_20
|View full text |Cite
|
Sign up to set email alerts
|

Can the postoperative follow-up visit be deferred up to four weeks after an uneventful cataract surgery? - A randomized controlled trial

Abstract: Purpose: The aim of this study was to compare the postoperative visual outcome after a Day 0 examination in patients with two follow-ups, one between Day 3 to Day 7 and other between Day 25 to Day 30 to those with a single ophthalmic follow-up directly after 25–30 Days and to assess the safety of deferral of the first follow-up visit at 1 week. Methods: Randomized Controlled Trial was conducted at a tertiary eye care hospital, with 848 patients enrolled for the study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A single surgeon performed all surgeries, while with multiple surgeons we would probably have had a wider palette of postoperative results. Another limitation was the short-term follow-up of the study groups, although several studies showed that 4 weeks after uneventful cataract surgery is enough time for follow-ups, as the visual outcome at the end of 1 month is optimal and the postoperative complications usually occur in the first 2 weeks [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single surgeon performed all surgeries, while with multiple surgeons we would probably have had a wider palette of postoperative results. Another limitation was the short-term follow-up of the study groups, although several studies showed that 4 weeks after uneventful cataract surgery is enough time for follow-ups, as the visual outcome at the end of 1 month is optimal and the postoperative complications usually occur in the first 2 weeks [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size is calculated as follows: 2[Zα + Z1 -β] 2 × (sd2/d2) = 2 [1.96 + 1.645 ] 2 × [(0.1125)2/(0.025)2] = 263 for one group, where reference mean values for postoperative visual outcomes are taken from the study conducted by Deshpande et al [25]. The number of participants in intervention group will be 263 and the number of participants in the control (reference) group will be 263.…”
Section: Sample Size and Sampling Techniquementioning
confidence: 99%
“…Meltzer et al [24] performed a study using data from the PRECOG (Prospective Review of Early Cataract Outcomes and Grading) trial and reported that visual acuity immediately after cataract surgery was highly correlated with visual acuity after 40 days, suggesting that for the purposes of quality assessment, follow-up of all patients is not needed. A study by Deshpande et al [25] concluded that visual outcomes after uneventful cataract surgery were comparable between patients followed up on days 3 to 7 and days 25 to 30 in comparison to patients directly followed up on days 25 to 30. Additionally, it was observed that the first follow-up visit could be safely deferred until 4 weeks after uneventful cataract surgery, including phacoemulsification or small-incision cataract surgery (SICS), in patients with no preexisting ocular or systemic comorbidity [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation